Differences between 48 and 72-hour intervals on match load and subsequent recovery: a report from the Brazilian under-20 national football team - Carolina Franco Wilke; Carolina Franco Wilke; Cândido Celso Coimbra; Filipe R. Drummond; Lucas Rios Drummond; Lucas Rios Drummond; Helton Oliveira Campos; Helton Oliveira Campos; Tane Kanope; Tane Kanope; Guilherme Passos Ramos; Guilherme Passos Ramos (Frontiers Media S.A., 2024)
PurposeTo compare the external and internal load and subsequent recovery of football players after international tournament matches separated by 48 h vs. 72 h.MethodsA total of 14 male football players from the Brazilian National Team, competing in the 2019 South American Under-20 Championship, participated in the study. Match load was quantified using GPS variables and perceived exertion ratings (1). Additionally, before and 13-15 h after each match, players answered questions about the number of hours and quality of sleep, recovery status, and muscle soreness (0-10) and provided a blood sample for creatine kinase and reactive C-protein analysis. Values of all variables were compared between matches played with 48-h intervals (matches 1-4) and 72-h intervals (matches 5-8).ResultsNo significant differences in performance or perceptual parameters were observed between matches (p = 0.136-0.953). However, CK was higher in matches 1-4 compared to matches 5 and 6; and ΔPCR was higher in matches 2 and 3 compared to matches 5 and 6, and in match 4 compared to matches 5 and 8.ConclusionsAfter matches with a 48-h rest interval, players showed increased markers of inflammation and muscle damage compared to matches with a 72-h rest interval.